(untitled) (Revista Brasileira Multidisciplinar, 2021)
Higher Education Institutions (HEI) have played a distinct role in society: they are predisposed to be at the forefront of social change and to deal with problems. The objective of this work was to identify how sustainability has been developed in HEI around the world, examining the evolution of management in environmental issues and the promotion of social change. The methodology used was content analysis, following the epoch approach to build a chronological narrative of the development of sustainability over the years. The results presented three periods of the global context of sustainability in the HEI. The first covered the phase of discovering sustainability between 1970 and 1990. The second period between 1990 and 2010 included the phase of adapting sustainability. Finally, the third season started in 2010 covered the implementation of sustainability in HEI. Understanding the development of sustainability in HEs during these years was essential to identify the current state of the art and to map future paths in the area.